The Relationship Between BPJS Health Service Quality And BPJS Patient Satisfaction In Class III Inpatient Installations At Rsu Imelda Indonesian Workers Medan In 2023 - Ritonga, Zulham Andi; Siregar, Miftahurrizky (CV. Devitara, 2024)
Quality of health services is the perfection of services in accordance with professional standards and health service standards, this aims to increase the satisfaction of patients who come for treatment. The aim of this research is to determine the relationship between the quality of BPJS health services and the satisfaction of BPJS patients in class III inpatient installations at the RSU Imelda Pekerja Indonesia Medan in 2023. This research method uses a quantitative correlation analytical type method with a cross sectional approach. The population in this study was 4,325 class III BPJS Health inpatient participants at RSU Imelda Pekerja Indonesia Medan. Based on the results of sample calculations using the Slovin formula, the sample to be studied was 98 respondents. The sampling technique in this research uses a probability sampling technique with a simple random sampling type. The research instrument uses a questionnaire created by researchers based on Tjiptono's (2017) theory. Data were analyzed using univariate analysis and bivariate analysis using the chi-square statistical test. The results of this study show the quality of BPJS health services with the satisfaction of BPJS patients in class III inpatient installations at RSU Imelda Pekerja Indonesia. The results obtained are reliability (p-value= 0.01), guarantee (p-value = 0.00), evidence physical (p-value = 0.00), empathy (p-value = 0.04), responsiveness (p-value = 0.02). It can be concluded that there is a relationship between the quality of BPJS Health services and the satisfaction of BPJS patients in the Class III Inpatient Installation at the RSU Imelda Pekerja Indonesia Medan in 2023. It is hoped that the results of this research can be input for the Imelda Workers Indonesia RSU to improve the quality of service, especially in the Inpatient Installation. One of the class III stays is improving facilities at the RSU Imelda Pekerja Indonesia Medan.